Bioethanol production-pretreatment of empty fruit bunch by enzymatic hydrolysis - 404273 Tan, Zee Sin; Ismail Mahmood, (supervisor) (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan Kimia) - Universiti Teknologi Malaysia, 2008